Tecnologias digitais e assistivas no contexto da deficiência visual: uma revisão de literatura - Escrivano, Ana Julia (Universidade Federal de São Carlos, 2024)
With the advent of technological innovations, there are many ways of accessing and interacting with the information available on digital networks. Thus, Digital Information and Communication Technologies (DICT) have emerged as a way of providing autonomy in different contexts of life in society, including education. In this sense, the aim of this research was to review the literature on digital and assistive technology resources that are generally used in the schooling of visually impaired students. In order to achieve this objective, the data was organized according to an adaptation of the procedures established by the Preferred Reporting Items for Systematics Review and Meta-Analysis (PRISMA) and treated qualitatively, by discussing the contributions of each of the studies. The electronic search was carried out in the Scientific Electronic Library Online (SciELO), Portal Periódicos da Capes and Brazilian Digital Library of Theses and Dissertations (BDTD) databases, using the following descriptors and Boolean operator: Digital Technology and Visual Impairment. Of the eight studies considered for analysis, three included technologies in the school context, three included software and mobile applications in the school context and two included software and mobile applications in the social context. The research analyzed indicated the need to overcome the adversities that hinder the autonomy of visually impaired students and highlighted the importance of the teacher in the process of using technological resources as a means of mediating the teaching-learning process. In addition, the data showed that technologies are being developed and made available to people with visual impairments. Therefore, the need to combine digital and assistive resources is highlighted, so that the respective users have greater accessibility when exploring the most varied devices, software, applications and content.
Digital and assistive technologies in the context of visual impairment: a literature review
Keywords: Educação especial; Tecnologias digitais; Tecnologia assistiva; Deficiência visual; CIENCIAS HUMANAS